Estudos Luso-Hispanos de História do Direito II = Estudios Luso-Hispanos de Historia del Derecho II - Álvarez-Gómez, Daniel (Historia del Derecho, 2021)
This book brings together a set of studies that were presented and discussed at the III Spanish-Portuguese Meeting of Law Historians. They deal with central themes of the History of Law and Institutions in Modern and Contemporary eras, with special emphasis on the peninsular territories and also on the territories that made up, at different times, the Spanish and Portuguese empires. As a whole, they contribute to broaden and deepen the historical knowledge of aspects related to justice and the administration of the territories, the functioning of institutions (courts, universities, courts) and the discussion of legal concepts central to the knowledge of the legal-political doctrine produced at different times of a vast chronological period.